Preliminary Study of the Gastric Acidity in Thoroughbred Horses at Rest after Enteral Administration of Esomeprazole Magnesium (Nexium) - Pereira, Marsel C. [UNESP]; Levy, Flavia L.; Valadao, Carlos A. A. [UNESP]; Ferraz, Guilherme C. [UNESP]; Queiroz-Neto, Antonio [UNESP] (Elsevier B.V., 2009)
The regulation of gastric secretion is of crucial importance to the equilibrium of the gastroenteric system. Despite the large number of factors involved in the causes of peptic illnesses, pH = 4 is considered the threshold between physiologic and deleterious effects of stomach acid secretion. With the aim of maintaining pH greater than 4, proton-pump inhibitors, such as esomeprazole magnesium (NEXIUM), have shown excellent results in the control of acid secretion. Aimed at examining the action of this drug in the control of pH levels of gastric secretion in thoroughbreds, a single dose of 40 or 80 mg of esomeprazole magnesium was administered daily, and pH was determined serially for 5 consecutive days. The results obtained corroborated the efficacy of esomeprazole magnesium in the control of gastric pH at both doses tested, with 100% of the mean pH being greater than 5. Moreover, no statistical difference was noted between the two doses tested.
Keywords: Esomeprazole magnesium; Proton pump inhibitors; gastric ulcer; Horse; Control of stomach acidity